Knee joint loading in the open and square stance tennis forehands - Sandamas, Paul (2013)
Sandamas, Paul 2013. Knee joint loading in the open and square stance tennis forehands. Department of Biology of Physical Activity, University of Jyväskylä. Master's Thesis in Biomechanics. 80 pages.